Identification and characterisation of fip37-4 suppressor mutants in Arabidopsis thaliana - Bridgen, Alexander John / AJB (2022)
Post-transcriptional and co-transcriptional RNA modifications play essential roles in controlling mRNA fate. The most abundant internal mRNA modification in eukaryotic cells is N6-methyladenosine (m6A) which has been shown to be critical for development in many eukaryotes and plays an important role influencing biological processes through its regulatory effects on RNA metabolism and translation. m6A is a dynamic modification with deposition of m6A on mRNA being catalysed by the methyltransferase “writer” complex, removed by demethylases “erasers” and recognised by m6A binding proteins known as “readers” which play specific regulatory roles. The Arabidopsis thaliana core m6A writer complex comprises of MTA (METTL3), MTB (METTL14), FIP37 (WTAP) VIRILIZER (VIRMA), HAKAI, HIZ1 and HIZ2 (likely homologue of ZC3H13). How m6A methylation machinery is regulated and knowledge of components mediating its various functions is still far from fully understood: especially in plants.